Estimation of benchmark performance standards: An application to public school expenditures - Dopuch, Nicholas; Gupta, Mahendra (Journal of Accounting and Economics, 1997)
The accounting and management literature reflects an increasing interest in relative performance evaluation (RPE) measures, often called ‘benchmarking’. In this paper we illustrate how stochastic frontier estimation (SFE) can be used to estimate benchmark performance standards which control for differences in the environments of the benchmarked operating units. Our application of SFE uses cross-sectional data reported by school districts in the state of Missouri for the year 1990–1991. The results suggest that the districts may have had as much as $394 million of excess expenditures in their operations.